2015
DOI: 10.1136/thoraxjnl-2014-206449
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind randomised placebo-controlled trial of bolus-dose vitamin D3supplementation in adults with asthma (ViDiAs)

Abstract: NCT00978315 (ClinicalTrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
125
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 27 publications
8
125
1
8
Order By: Relevance
“…79,80,82 In addition, vitamin D significantly reduced the risk of patients having at least 1 emergency visit or hospitalization for an exacerbation (OR, 0.39; 95% CI, 0.19-0.78). 77,79,80,82,84,87 These effects are mainly attributable to studies performed in adults. Therefore, generalization of these results to children should be done with caution.…”
Section: 7881mentioning
confidence: 99%
See 3 more Smart Citations
“…79,80,82 In addition, vitamin D significantly reduced the risk of patients having at least 1 emergency visit or hospitalization for an exacerbation (OR, 0.39; 95% CI, 0.19-0.78). 77,79,80,82,84,87 These effects are mainly attributable to studies performed in adults. Therefore, generalization of these results to children should be done with caution.…”
Section: 7881mentioning
confidence: 99%
“…Vitamin D supplementation significantly reduced the rate of asthma exacerbations treated with systemic corticosteroids (odds ratio [OR], 0.63; 95% CI, 0.45-0.88) 79,80,82,87 and tended to increase the time to first exacerbation (P = 0.052). 79,80,82 In addition, vitamin D significantly reduced the risk of patients having at least 1 emergency visit or hospitalization for an exacerbation (OR, 0.39; 95% CI, 0.19-0.78).…”
Section: 7881mentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent Cochrane systematic review metaanalysis found two RCTs that studied the efficacy of vitamin D supplementation in the treatment of adults with mild-tomoderate asthma [15]. Vitamin D supplementation with oral vitamin D3, 100,000 IU bolus once, then 4000 IU/day for 28 weeks in VIDA study [16] and bimonthly 6 mL Vigantol oil containing 120,000 IU vitamin D3 for 12 months (total of six doses) in ViDiAs study [17] did not reduce asthma exacerbations. None of these powerful high-quality RCTs support the usefulness of vitamin D supplementation in the treatment of asthma in order to reduce the number of exacerbations or improve the health-related quality of life of patients.…”
Section: Vitamin Dmentioning
confidence: 99%